2018
DOI: 10.1038/s41467-018-07281-z
|View full text |Cite
|
Sign up to set email alerts
|

Design of an inherently-stable water oxidation catalyst

Abstract: While molecular water-oxidation catalysts are remarkably rapid, oxidative and hydrolytic processes in water can convert their active transition metals to colloidal metal oxides or hydroxides that, while quite reactive, are insoluble or susceptible to precipitation. In response, we propose using oxidatively-inert ligands to harness the metal oxides themselves. This approach is demonstrated by covalently attaching entirely inorganic oxo-donor ligands (polyoxometalates) to 3-nm hematite cores, giving soluble anio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 62 publications
9
78
0
Order By: Relevance
“…In this context, we recently reported that the oxidatively inert heteropolytungstate (POM) cluster anion [α‐PW 11 O 39 Fe III ] 4− ‐O − could serve as a covalently attached oxo donor ligand for hematite Fe 2 O 3 NCs, giving water‐soluble complexes 1 (Figure b), uniquely positioned between molecular catalysts with iron active sites (Figure a) and α‐Fe 2 O 3 photoanodes (Figure c) . Notably, 1 is not only water‐soluble, but also inherently stable to oxidation and hydrolysis.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…In this context, we recently reported that the oxidatively inert heteropolytungstate (POM) cluster anion [α‐PW 11 O 39 Fe III ] 4− ‐O − could serve as a covalently attached oxo donor ligand for hematite Fe 2 O 3 NCs, giving water‐soluble complexes 1 (Figure b), uniquely positioned between molecular catalysts with iron active sites (Figure a) and α‐Fe 2 O 3 photoanodes (Figure c) . Notably, 1 is not only water‐soluble, but also inherently stable to oxidation and hydrolysis.…”
Section: Figurementioning
confidence: 99%
“…Notably, 1 is not only water‐soluble, but also inherently stable to oxidation and hydrolysis. As such it can catalyze visible‐light‐driven water oxidation for an entire week under turnover conditions with no decrease in activity …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Note that while the POMs in these systems are currently not considered the reactive WOC sites, they are nevertheless the sine qua non, without which the whole system would not be able to operate. Given the high technological potential of these composites for surface deposition, electrode immobilization or photoelectrode incorporation, a wide array of chemical modification possibilities has now become accessible and requires urgent research attention [102][103][104]. In addition, recent ground-breaking studies have shown that external stimuli, such as radio-frequency electromagnetic fields [105] or permanent magnetic fields [106], could be used to enhance the activities of WOCs.…”
Section: Outlook and Future Directionsmentioning
confidence: 99%
“…Given the high technological potential of these composites for surface deposition, electrode immobilization or photoelectrode incorporation, a wide array of chemical modification possibilities has now become accessible and requires urgent research attention. [102][103][104] In addition, recent ground-breaking studies have shown that external stimuli such as radio-frequency electromagnetic fields [105] or permanent magnetic fields [106] could be used to enhance the activity of WOCs. These and similar concepts could in future be used to fine-tune and optimize industrial water electrolysis.…”
Section: Outlook and Future Directionsmentioning
confidence: 99%